Can probiotics be protective and growth-promoting to coffee plants? - de Freitas, Guilherme Peixoto [UNESP]; Patricio, Flávia Rodrigues Alves; Vargas, Rafaela Carvalho [UNESP]; Bettiol, Wagner [UNESP] (Springer Nature, 2025)
Probiotics show well-documented benefits to animal and human health and are safe for organisms and the environment. This study explored the potential of five commercial probiotics - Colostrum® BS Liquid, Colostrum® BS Powder, Colostrum® BIO 21 Liquid, and Colostrum® BIO 21 MIX Powder (widely used in poultry production), and Enterogermina® (used for humans) in managing coffee leaf rust (CLR), brown eye spot (BES), bacterial leaf blight (BHB) and dieback, as well as their effect on coffee seedlings growth. In vitro experiments revealed that only Colostrum® BIO 21 Liquid completely inhibited urediniospores germination of Hemileia vastatrix, CLR causal agent, while the other probiotics showed partial inhibition. Colostrum® BS Powder, partially inhibited Cercospora coffeicola (BES causal agent) and Boeremia coffea (dieback causal agent) mycelial growth. Colostrum® BS Powder and Colostrum® BIO 21 MIX Powder, containing Bacillus sp. and lactic acid bacteria, significantly reduced the severity of CLR, dieback and showed some effectiveness against BHB (caused by Pseudomonas syringae pv. garcae). None of the tested probiotics reduced BES severity. Beyond disease control, Colostrum® BS Powder and Colostrum® BIO 21 MIX Powder consistently enhanced coffee seedling growth parameters, including shoot and root biomass, root volume, and leaf characteristics, in both cell trays and rhizotrons. Conversely, liquid formulations and Enterogermina® generally did not show significant benefits for disease control or plant growth promotion. These findings suggest that Colostrum® BS Powder and Colostrum® BIO 21 MIX Powder, that are safe for the environment and have their mass production well developed, could offer a promising, eco-friendly approach to enhancing plant health and coffee seedling growth. After further studies in field conditions they can become important tools to improve sustainable coffee production.